Moving past the sound-noise dichotomy: How professionals of the built environment approach the sonic dimension. (January 2023) - Steele, Daniel; Bild, Edda; Guastavino, Catherine
Abstract: Debates on the sounds of cities have focused on the often-used dichotomy of noise versus sound; yet for the decades of debate, few examples of policy, procedures, or case studies have made motions in acknowledging the diverse roles that sound plays in shaping our experience and understanding of the city: orienting us, creating memories, fostering healthy restoration, etc. To better understand the challenges that professionals of the built environment face in their everyday practice, we interview 22 professionals across six countries to understand how they interact with sound. Building on a substantial corpus of transcriptions using an multi-layered coding process, three approaches of how sound is considered and prioritized in practice emerged: policy, public health, and city user experience. These three approaches are operationalized according to the key concepts, decision criteria, and evaluation methods that frame what motivates each professional to consider sound in the context of individual projects. Finally, these considerations were heavily influenced by contextual factors including individual, locational, and organizational. Classifying the ways in which professionals consider sound in practice into these three approaches may serve as a better starting point for future communication and collaborations between research and practice. Further, it may better accommodate the inclusion of other types of artists and experts into the conversation on urban sound. Highlights: Professionals of the built environment (PBEs) face challenges in integrating sound in everyday projects. Sound is considered using three approaches: policy, public health, and city user experience. Each approach is context-dependent (individual, location, organization) and can rely on human- or object-centered evaluation The identified approaches could guide future communication and collaboration between sound experts and urban professionals